Kajian tentang Komunikasi dan Budaya - Sunata, Ivan (Institut Agama Islam Negeri Kerinci, 2023)
The purposed of this reaserch was to explore the thoughts and opinions of the experts in the field of communication about the relationship between communication and culture. The results of the resecarch revealed that: the culture as a system will give affect to communication. Because, the basic of communication is the culture that exists in society. Besides, the communicator's cultural context will affect every part and every pattern of communication activity. There were three reasons why culture influences communication: culture teaches meaningful rules, rituals and procedures, culture reinforces values, culture teaches relationships with other individuals